Teduglutide-induced stem cell function in intestinal repair. (4th May 2018) - Sipos, Ferenc; Műzes, Györgyi
ABSTRACT: Malabsorption is a major and common clinical characteristics of short bowel syndrome (SBS) and inflammatory bowel diseases (IBD). Traditional treatment opportunities have focused on decreasing malabsorptive losses via dietary modifications and antisecretory/antidiarrheal agents. However, novel therapeutic modalities aim to enhance the absorptive capacity of the residual bowel by the administration of different intestinal growth factors including teduglutide. In a current study the existence of two distinct functional putative epithelial stem cell subpopulations (i.e. Lgr5 + /Bmi1 − and Lgr5 − /Bmi1 + ) have been described in a rat model of ileal resection and anastomosis. The described epithelial stem cell subpopulations displayed distinct behaviour after surgical injury and teduglutide administration. Though teduglutide was found to be clinically effective, we must keep in mind that growth factors theoretically may provoke adenoma development and subsequent malignant transformation. The present results give us a better insight into the role of stem cell modulation in intestinal repair. Based on these results new perioperative adjuvant pharmacological approaches may be developed for SBS and IBD patients to reduce the clinical symptoms and complications of associated malabsorption.